LEARNING LOSS IN ONLINE WRITING INSTRUCTIONAL PROCESS - Imaniar, Restu; Andang Saehu; Juhana (ENGLISH, 2024)
This qualitative study focused on reporting online teaching and learning English writing and identifying the reasons beyond learning loss in the pandemic. It focused on 50 third-grade students, 4 English teachers, and 5 parents at an upper secondary school level in Sukabumi. They were selected purposively. The instruments used were questionnaires, observations, and interviews. The results revealed that online learning significantly changed the teaching preparation and process. Teachers and students had to adapt to new pedagogical approaches, from face-to-face to online classes. Effective online English learning requires well-structured, scheduled, and coordinated learning activities to enhance effectiveness. The pandemic posed challenges to online learning, including technological issues, a lack of discipline, and creative activities. English learners faced difficulties such as collaborative planning, accessibility issues, and multimedia resource use, whereas parents and teachers faced difficulties in supervising and managing work schedules and providing support. Online education had a significant impact on English learning, enhancing interaction through complicated materials and addressing the lack of face-to-face interaction and internet connectivity.